Philippine gay culture : the last thirty years : binabae to bakla, silahis to MSM - Garcia, J. Neil C. (Quezon City, Philippines : UP Press, 1996)
Phillipine Gay Culture is a descriptive survey of popular and academic writings on and by Filipino male homosexuals, as well as a genealogy of discourses of male homosexuality and the bakla and/or gay identities that emerged in urban Philippines from the 1960s to the present. This conceptual history engages recent events in the Philippines$1 (Bsexually self-aware present, but also explores colonial history in showing how modernity implanted a new sexual order of (3z(Bhomo/hetero(3y (Band further marginalized the effeminate local identity of bakla. Garcia analyzes several works by bakla writers and artists that narrate hybridity, appropriation, and postcolonial resistance and in their own way, enriched Philippine gay culture and the Philippines as a whole. This book will appeal to scholars of literary history, postcolonial studies, cultural studies, gender studies, and Asian history.s
PART ONE: Philippine gay culture: the last thirty years -- PART TWO: The early gay writers Montano, Nadres, Perez.
Includes bibliographical references and index.
Keywords: HOMOSEXUALITY -- PHILIPPINES